All-cause and cardiovascular mortality in a consecutive series of patients with diabetic foot osteomyelitis. (September 2017) - Ricci, Lucia; Scatena, Alessia; Tacconi, Danilo; Ventoruzzo, Giorgio; Liistro, Francesco; Bolognese, Leonardo; Monami, Matteo; Mannucci, Edoardo
Highlights: There are few studies on mortality in patients with diabetic foot osteomyelitis (DFO). In the present study, mortality in patients with DFO is much higher than that reported in clinical series of patients with diabetic foot ulcers. Mortality in patients with DFO is higher when hindfoot is affected. The majority of deaths were attributed to cardiovascular causes, and not directly to infections. Yearly mortality rate in this study was 13%, which is similar to that of very aggressive cancer. Abstract: Background: Mortality in patients with type 2 diabetes and diabetic foot osteomyelitis (DFO) have been explored in few small studies with a short follow-up. Aim of the present study is to assess all-cause and cardiovascular mortality and predictors of mortality in a consecutive series of patients with DFO. Research design and methods: Patients with a diagnosis of DFO, attending the Diabetic Foot Unit of San Donato Hospital in Arezzo between January 1st, 2012 and December 31st, 2013, were included in this retrospective study. Information on all-cause mortality up to December 1st, 2016, was obtained from the registry of the Local Health Unit of Arezzo, which contains updated records of all persons living in Tuscany. Results: One hundred ninety-four patients were included in the study. During a mean period of observation of 2.8 ± 1.4 years, 73 (37.6%) died, with a yearly rate of 13.2%. Of the 73 deaths, 59 were attributable to cardiovascular causes. After adjusting for possible confounders in a Cox analysis, site of osteomyelitis (hindfoot vs mid/forefoot) was associated with a higher mortality, and surgical treatment with a lower mortality. Conclusions: Mortality in patients with DFO appears to be much higher than that reported in clinical series of patients with diabetic foot ulcers, particularly when hindfoot is affected.